Primary progressive aphasias associated with C9orf72 expansions: Another side of the story. (December 2021) - Saracino, Dario; Géraudie, Amandine; Remes, Anne M.; Ferrieux, Sophie; Noguès-Lassiaille, Marie; Bottani, Simona; Cipriano, Lorenzo; Houot, Marion; Funkiewiez, Aurélie; Camuzat, Agnès; Rinaldi, Daisy; Teichmann, Marc; et al.
Abstract: C9orf72 repeat expansions are rarely associated with primary progressive aphasias (PPA). In-depth characterization of the linguistic deficits, and the underlying patterns of grey-matter atrophy in PPA associated with the C9orf72 expansions (PPA- C9orf72 ) are currently lacking. In this study, we comprehensively analyzed a unique series of 16 patients affected by PPA- C9orf72 . Eleven patients were issued from two independent French and Finnish cohorts, and five were identified by means of literature review. Voxel-based morphometry (VBM) studies were performed on three of them. This study depicts the spectrum of C9orf72 –related aphasic phenotypes, and illustrates their linguistic presentation. The non-fluent/agrammatic variant was the most frequent phenotype in our series (9/16 patients, 56%), with apraxia of speech being the main defining feature. Left frontal lobe atrophy was present in these subjects, peaking in inferior frontal gyrus. Three patients (19%) showed the semantic variant, with progression of atrophy in temporo-polar regions, later involving orbitofrontal cortex. Anterior temporal lobe dysfunction was also particularly relevant in two patients (12.5%) with mixed forms of PPA. Lastly, two patients (12.5%) had unclassifiable PPA with predominating word-finding difficulties. No PPA- C9orf72 patients in our series fulfilled the criteria of the logopenic variant. Importantly, this study underlines the role of C9orf72 mutation in the disruption of the most anterior parts of the language network, including prefrontal and temporo-polar areas. It provides guidelines for C9orf72 testing in PPA patients, with important clinical impact as gene-specific therapies are upcoming.